ACUTE TRACHEAL INJURY - U.B. Berkinov; S.P. Khalikov; M.R. Karimov; L.A. Butaev (Central Asian Journal of Medicine, 2023)
The purpose of this article is to examine the importance of improved coordination of care by an interprofessional team to improve outcomes for patients with tracheal injuries. Tracheal trauma is a time-dependent, high-risk acute condition that can adversely affect the patient’s ability to maintain a patent airway. Optimal initial stabilization requires a team approach that includes emergency medicine, ENT, and ancillary services including respiratory therapy. Curative treatment, which involves emergency surgery, has been shown to lead to positive outcomes, as opposed to watchful waiting, which is associated with worse outcomes. The review article provides data on the diagnosis, methods and results of treatment of patients with acute trauma to the trachea and main bronchi. It is noted that only timely diagnosis, adequate surgical and anesthetic care can ensure a favorable treatment outcome.